Effects of symptom clusters and depression on the quality of life in patients with advanced lung cancer - Choi, S.; Ryu, E. (European journal of cancer care, 2018)
People with advanced lung cancer experience later symptoms after treatment that is related to poorer psychosocial and quality of life (QOL) outcomes. The purpose of this study was to identify the effect of symptom clusters and depression on the QOL of patients with advanced lung cancer. A sample of 178 patients with advanced lung cancer at the National Cancer Center in Korea completed a demographic questionnaire, the M.D. Anderson Symptom Inventory–Lung Cancer, the Center for Epidemiological Studies Depression Scale, and the Functional Assessment of Cancer Therapy–General scale. The most frequently experienced symptom was fatigue, anguish was the most severe symptom‐associated distress, and 28.9% of participants were clinically depressed. Factor analysis was used to identify symptom clusters based on the severity of patients' symptom experiences. Three symptom clusters were identified: treatment‐associated, lung cancer and psychological symptom clusters. The regression model found a significant negative impact on QOL for depression and lung cancer symptom cluster. Age as the control variable was found to be significant impact on QOL. Therefore, psychological screening and appropriate intervention is an essential part of advanced cancer care. Both pharmacological and non‐pharmacological approaches for alleviating depression may help to improve the QOL of lung cancer patients.